Sistem Informasi Pemesan Dan Penyewaan Jasa Fotografi 4g Studio Salakan - Yeti Kule; Maharani Maharani (Akademi Manajemen Informatika dan Komputer Luwuk Banggai, 2022)
The problem that was obtained during this research was that the ordering and rental process at the 4G Studio Salakan still uses a manual and simple process where tenants come directly to the studio so that the service is still not as maximal as possible. The research method used in the preparation of the Final Project is the field method. The interview method (Interview method) and the library method (library Method). The results of this study are that the authors can create a system or web-based application program that helps 4G studio Salakan in ordering and leasing and publishing information, as well as helping disseminate information effectively and efficiently.